Entrepreneurial skills of students of polytechnic higher education in Portugal: Business influences - Gomes, José Hermínio Gonçalves (2016)
Introduction: Most of entrepreneurial ideas does not appear ready or over. Any business opportunity needs to be developed and improved throughout the enterprise process. Educational institutions may facilitate the ability of the students had undertaken, identifying and building business opportunities, enhancing their knowledge and formative experiences along the learning process. Objectives: Evaluate the business influences the entrepreneurial ability of students of the Polytechnic. Methodology: Correlational quantitative study, conducted with 1604 students from 18 institutions of the Polytechnic of Portugal. Data collection took place between July and November/2015, with a questionnaire to assess the entrepreneurial profile, Carland Entrepreneurship Index (CEI) and sociodemographic variables of students. Results: We found four business factors that influence entrepreneurship, "availability of funds" (4:13, SD = .67); "Have stable customers and incentives" (3.99, SD = .58); "Social and economic instability" (3:08, SD = 1.17) and "opportunities in the sector and area of residence" (3:36, SD = 1.05). On a scale range between (1-5), we obtained an overall score of 3.86 (SD = .55), for the corporate influences on entrepreneurship. Conclusion: For students entrepreneurial influences are important, with a greater sense of fear with regard to economic instability, reinforcing the need for further training and academic investment in the business.